2013
DOI: 10.3390/ijms14047716
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin in High-Density Lipoproteins: Structural Role and Biological Function

Abstract: High-density lipoprotein (HDL) levels are an inverse risk factor for cardiovascular diseases, and sphingomyelin (SM) is the second most abundant phospholipid component and the major sphingolipid in HDL. Considering the marked presence of SM, the present review has focused on the current knowledge about this phospholipid by addressing its variable distribution among HDL lipoparticles, how they acquire this phospholipid, and the important role that SM plays in regulating their fluidity and cholesterol efflux fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 180 publications
0
52
0
1
Order By: Relevance
“…The fluidity of the HDL, as well as its CEC, is considered to be inversely related to the sphingomyelin content of the HDL. The sphingomyelin content of the HDL subpopulations remains, at present, controversial . The complexity of sphingomyelin species, their distribution in the different HDL particles, and their role in HDL fluidity and CEC is considered a promising target for future studies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluidity of the HDL, as well as its CEC, is considered to be inversely related to the sphingomyelin content of the HDL. The sphingomyelin content of the HDL subpopulations remains, at present, controversial . The complexity of sphingomyelin species, their distribution in the different HDL particles, and their role in HDL fluidity and CEC is considered a promising target for future studies …”
Section: Discussionmentioning
confidence: 99%
“…[47] The complexity of sphingomyelin species, their distribution in the different HDL particles, and their role in HDL fluidity and CEC is considered a promising target for future studies. [47] Our study has limitations. First, cholesterol efflux was measured ex vivo, but the transport of the cholesterol to the liver, the second part of the reverse cholesterol transport was not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingomyelin is a constituent of all lipoproteins and affects HDL-mediated cholesterol efflux, hepatic cholesterol uptake, clearance of triglyceride rich remnants, aggregation and binding of LDL to the aterial wall [4446]. Further research is needed to clarify whether reduced hepatic cholesterol is a consequence of low sphingomyelin in these animals.…”
Section: Discussionmentioning
confidence: 99%
“…By decreasing the fluidity of HDLs but enhancing the affinity for cholesterol, increases in the sphingomyelin content of HDLs have a complex effect on cholesterol efflux capacity. 28, 238 One study reported an inverse association between sphingomyelin in HDL and the presence of CAD in women. 239 Because of their cytoprotective activities, S1P and other lysosphingolipids are especially interesting candidates to explain HDL dysfunction and to be used as underlying biomarkers.…”
Section: Post-translational Modifications Of Proteinsmentioning
confidence: 99%